Beta-adrenergic pathway activation enhances aggressiveness and inhibits stemness in head and neck cancer - Lopes-Santos, Gabriela [UNESP]; Bernabé, Daniel Galera [UNESP]; Miyahara, Glauco Issamu [UNESP]; Tjioe, Kellen Cristine [UNESP] (My University, 2021)
Chronic stress leads to the activation of the beta-adrenergic pathway. Its activation has been implicated in the progression of different types of cancer but its role on head and neck squamous cell carcinomas (HNSCCs) remains undefined. The aim of this study was to investigate the influence of the beta-adrenergic pathway activation in the progression of HNSCCs and offer a panel of potential treatments for patients with the active beta-adrenergic pathway. Five hundred and twenty TCGA patients with primary HNSCCs were divided in two groups: ADRB2low / SLC6A2low and ADRB2high / SLC6A2high. Differentially expressed genes (DEGs) were identified through differential expression analysis. The association of clinicopathological and genomic features between the groups was analyzed using a bioinformatic approach. Potential drugs for treatment of HNSCC were identified based on the DEGs. There was association between ADRB2 and SLC6A2 expressions with age, race, tumor site, histologic grade, perineural invasion, and HPV p16 status. It was identified 898 DEGs between the groups. High ADRB2/SLC6A2 expression stimulated HNSCC proliferation, adhesion, invasion, and angiogenesis. On the other hand, genes related to cell stemness were downregulated in patients with activation of the beta- adrenergic pathway. Finally, 56 FDA-approved antineoplastic and immunotherapeutic drugs were identified as potential targets for the personalized treatment.
Keywords: Beta-adrenergic receptors; Head and Neck Squamous Cell Carcinoma; Norepinephrine Transport Protein; Psychological stress